A polyurethane composite material for power transmission tower and preparation method thereof
By using polyurethane composite materials, combined with bio-based polyurethane and modified dolomite and other raw materials, the mechanical properties of the transmission pole tower materials are improved, the problems of easy deformation and cracking of traditional materials are solved, and the safety and reliability of the transmission pole towers are improved.
Patent Information
- Application Number
- CN202510026304.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-08
AI Technical Summary
Traditional transmission pole tower materials are prone to deformation, cracking or flashover accidents, and require a large amount of manpower and material investment during transportation, construction and maintenance, which affects the safety, economy and reliability of line construction.
A polyurethane composite material is used, which consists of polyurethane, bio-based polyurethane, glass fiber, modified dolomite, graphene, lubricant, antioxidant and mold release agent. The mechanical properties of the material are improved through specific proportions and preparation methods.
The polyurethane composite material significantly improves mechanical properties, can effectively improve the compatibility and filling effect of the material, increase the strength and toughness of the material, reduce the risks of deformation and cracking, and improve the safety and reliability of the transmission pole tower.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a polyurethane composite material for a power transmission tower and a preparation method thereof. Background Art
[0002] The pole tower is an important equipment for power transmission lines. Traditional transmission and distribution line pole towers mainly include concrete poles, wooden poles, steel pipe poles, and iron towers. These materials are prone to deformation, cracking, or various flashover accidents. The transportation, construction, and maintenance of the pole towers require a large investment of manpower and material resources, which directly affects the safety, economy, and reliability of line construction. At present, the research on transmission pole towers has begun to move towards high performance and lightweight. Composite materials have become a hot topic of research due to their light weight, high strength, corrosion resistance, high and low temperature resistance, and insulation.
[0003] Thermoplastic polyurethane (TPU) elastomer is a (AB)n block linear polymer, composed of flexible soft segments and rigid hard segments. Due to its advantages of high strength, good toughness, wear resistance, and cold resistance, it is often mixed with reinforcing materials such as glass fiber and ultra-high molecular weight polyethylene for the preparation of transmission tower materials. However, the bonding between the reinforcing material and the resin matrix will directly affect the mechanical properties of the composite material, so it is necessary to improve the formula of the composite material to obtain better mechanical properties. Summary of the invention
[0004] The first object of the present invention is to provide a polyurethane composite material for a transmission tower, wherein the composite material has excellent mechanical properties.
[0005] The second object of the present invention is to provide a method for preparing a polyurethane composite material for a transmission tower, which is simple and easy to operate.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A polyurethane composite material for a power transmission tower comprises the following raw materials, measured in parts by weight: 45-60 parts of polyurethane, 10-15 parts of bio-based polyurethane, 25-30 parts of glass fiber, 1-3 parts of modified dolomite, 0.1-0.5 parts of graphene, 0.1-0.5 parts of lubricant, 0.5-1.5 parts of antioxidant and 1-3 parts of release agent.
[0008] Furthermore, the preparation method of the bio-based polyurethane is as follows:
[0009]
[0010] (1) adding chelidonic acid, 4-chloro-1-butene, and triethylamine to a mixed solution of DMSO and acetone for heating reaction, and obtaining compound A after purification; adding compound A and meta-chloroperbenzoic acid to dichloromethane for reaction, and obtaining compound B after purification;
[0011] (2) Add compound B and tetraethylammonium bromide to dichloromethane, and introduce CO under nitrogen protection. 2 The mixture was stirred, washed and vacuum dried to obtain compound C;
[0012] (3) Compound C and 1,6-hexanediamine are added to DMF for reaction, and then washed and vacuum dried to obtain the product.
[0013] Furthermore, the average molecular weight of the bio-based polyurethane is 5000-6000 g / mol.
[0014] Furthermore, in step (2), the amount ratio of compound B, tetraethylammonium bromide and dichloromethane is 1 g: (0.05-0.15) g: (3-5) mL; the CO 2 The pressure of the reaction system is increased to 4-5 MPa; the stirring temperature is 110-120°C, and the stirring time is 22-26 hours.
[0015] Furthermore, in step (3), the usage ratio of compound C, 1,6-hexanediamine and DMF is 1 g: (0.2-0.4) g: (0.3-0.5) mL; the reaction temperature is 155-160° C., and the reaction time is 24-32 h.
[0016] Furthermore, in step (1), the mass ratio of chelidonic acid, 4-chloro-1-butene and triethylamine is 1:(2-3):(3-6); the volume ratio of DMSO and acetone in the DMSO and acetone mixed solution is 1:2; and the mass ratio of compound A and meta-chloroperbenzoic acid is 1:(2-3).
[0017] Furthermore, in step (1), the temperature of the heating reaction is 170-180°C, and the heating reaction time is 32-36 hours; the temperature of the reaction is 25-30°C, and the reaction time is 4-5 days.
[0018] Furthermore, the preparation method of the modified dolomite is as follows:
[0019] The dolomite is dispersed in the calcium lignin sulfonate solution and the pH is adjusted to 6-9, and the mixture is stirred and reacted at room temperature for 24-36 hours, and then filtered and dried to obtain the product.
[0020] Furthermore, the dosage ratio of the dolomite to the calcium lignin sulfonate solution is 1 g: (45-55) mL; and the concentration of the calcium lignin sulfonate solution is 1 g / L.
[0021] Furthermore, the polyurethane is a thermoplastic polyurethane elastomer; the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester; the release agent is Taoxi 3527; and the lubricant is sodium stearate.
[0022] Furthermore, the length of the glass fiber is 25-50 mm, and the specific surface area of the graphene is 260-350 m 2 / g, pH value is 6-8, and particle size is less than 10μm.
[0023] The method for preparing the polyurethane composite material for transmission towers comprises the following steps:
[0024] According to the weight ratio, polyurethane, bio-based polyurethane, glass fiber, modified dolomite, graphene, lubricant, antioxidant and release agent are uniformly mixed, stirred at 160-175° C. and 200-500 rpm for 10-12 hours, and then poured and cured to form.
[0025] Compared with the prior art, the beneficial effects of the present invention are mainly:
[0026] 1. The polyurethane composite material for power transmission towers of the present invention includes raw materials such as bio-based polyurethane and modified dolomite. And the test results show that the combination of bio-based polyurethane and modified dolomite can effectively improve the mechanical properties of polyurethane composite materials. This is because the dolomite modified by lignin can interact with the polyurethane matrix and glass fiber, effectively improve the compatibility of dolomite with the polyurethane matrix, improve the filling effect of dolomite, and thus increase the mechanical properties of the polyurethane composite material; while the low molecular weight bio-based polyurethane contains functional groups such as hydroxyl and carbamate, which can interact with the polyurethane matrix, reduce the agglomeration force between polyurethanes, thereby improving its dispersibility; at the same time, the molecular chain of low molecular weight bio-based polyurethane is shorter, and it is easier to interact with inorganic materials such as glass fiber, improve the compatibility between the polyurethane matrix and the glass fiber, and can also form a stronger interface bonding force, thereby improving the mechanical properties of the polyurethane composite material.
[0027] 2. The polyurethane composite material obtained by the present invention has excellent mechanical properties. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0029] The length of the glass fiber involved in the present invention is 25-50 mm; the specific surface area of the graphene is 260-350 m 2 / g, pH value is 6-8, particle size is less than 10μm; polyurethane is thermoplastic polyurethane elastomer.
[0030] Example 1
[0031] Example 1 provides a polyurethane composite material for transmission towers, which is composed of the following raw materials, in parts by weight: 50 parts of polyurethane, 12 parts of bio-based polyurethane, 27 parts of glass fiber, 2 parts of modified dolomite, 0.4 parts of graphene, 0.2 parts of sodium stearate, 1 part of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 35272 parts of Dow Hematite.
[0032] The preparation method of the above bio-based polyurethane is as follows:
[0033]
[0034] (1) Chelidonic acid, 4-chloro-1-butene and triethylamine were added to a mixed solution of DMSO and acetone (the volume ratio of DMSO and acetone was 1:2) in a mass ratio of 1:2.5:4, and heated at 175°C for 34 hours. After the reaction, the precipitate was removed by filtration, and the acetone, triethylamine and unreacted 4-chloro-1-butene were removed by rotary evaporation. Then, dichloromethane was used for extraction, and D was removed by washing with water. MSO, dried with anhydrous magnesium sulfate, and rotary evaporated again to remove dichloromethane to obtain compound A; according to the mass ratio of compound A to meta-chloroperbenzoic acid of 1:2.5, compound A and meta-chloroperbenzoic acid were added to DCM, reacted at 26°C for 4.5 days, the reaction solution was filtered, washed with 10% sodium sulfate solution, 10% sodium carbonate solution and distilled water in sequence, and then dried with anhydrous magnesium sulfate, and then concentrated by rotary evaporation, washed with ether, and recrystallized to obtain compound B.
[0035] The NMR results of compound B are:
[0036] 1H-NMR (400 MHz, DMSO) δ=1.77 (m, 4H), 2.37-2.46 (m, 4H), 2.62 (m, 2H), 4.15 (t, 4H), 6.99 (s, 2H); mass spectrometry analysis MS (ESI+): [M+H]+ calculated as 325.08, found as 325.08; the above results confirmed that the obtained product was the target product.
[0037] (2) Compound B and tetraethylammonium bromide were added to dichloromethane in a ratio of 1 g:0.1 g:4 mL. The mixture was then transferred to a high-pressure reactor and CO was introduced under nitrogen protection. 2 The pressure in the autoclave was raised to 4.5 MPa, and the mixture was stirred at 115 °C for 24 h. After the autoclave was cooled to room temperature, the remaining CO was released. 2 The mixture was reduced to normal pressure, washed with dichloromethane, and then dried in a vacuum oven at 30°C for 24 h to obtain compound C.
[0038] (3) Compound C, 1,6-hexanediamine and DMF were placed in a three-necked flask in a ratio of 1 g:0.3 g:0.4 mL, and reacted at 160°C in a nitrogen atmosphere for 24 h. The mixture was washed with deionized water and dried in a vacuum oven at 80°C for 24 h to obtain the product.
[0039] The NMR results of bio-based polyurethane are:
[0040] 1 H-NMR (400MHz, DMSO) δ=1.28-1.31(m,6H),1.40-1.52(m,4H),1.79-1.88(m,4H),2.55(t,2H),3.20-3.22(m,2H),3.64-3. 70(m,2H),4.10-4.15(m,6H),4.35(m,1H),4.59(m,1H),4.96(s,1H),5.39(s,1H),6.99(s,2H),7.59(s,2H); GPC:Mn=5210 g / mol.
[0041] The preparation method of the above-mentioned modified dolomite is as follows:
[0042] According to the dosage ratio of dolomite and calcium lignin sulfonate solution of 1g:50mL, the dolomite is dispersed in the calcium lignin sulfonate solution with a concentration of 1g / L and the pH is adjusted to 7, and the reaction is stirred at room temperature for 30h, and then filtered and dried to obtain the product.
[0043] Example 1 also provides a method for preparing the polyurethane composite material for power transmission towers, which is as follows:
[0044] According to the above weight ratio, polyurethane, bio-based polyurethane, glass fiber, modified dolomite, graphene, sodium stearate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and Taoxi 3527 are evenly mixed in a stirrer, stirred at 170° C. and 400 rpm for 11 hours, and then poured and cured to form.
[0045] Example 2
[0046] Example 2 provides a polyurethane composite material for transmission towers, which is composed of the following raw materials, in parts by weight: 60 parts of polyurethane, 15 parts of bio-based polyurethane, 30 parts of glass fiber, 3 parts of modified dolomite, 0.5 parts of graphene, 0.5 parts of sodium stearate, 1.5 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 3 parts of Taoxi 3527.
[0047] The preparation method of the above bio-based polyurethane is as follows:
[0048]
[0049] (1) According to the mass ratio of chelidonic acid, 4-chloro-1-butene and triethylamine of 1:3:6, chelidonic acid, 4-chloro-1-butene and triethylamine were added to a mixed solution of DMSO and acetone (the volume ratio of DMSO and acetone was 1:2), and heated at 180°C for 32 hours. After the reaction, the precipitate was removed by filtration, and the acetone, triethylamine and unreacted 4-chloro-1-butene were removed by rotary evaporation, followed by extraction with dichloromethane, washing with water, and removing DMSO, dried over anhydrous magnesium sulfate, and rotary evaporated again to remove dichloromethane to obtain compound A; according to the mass ratio of compound A to meta-chloroperbenzoic acid of 1:3, compound A and meta-chloroperbenzoic acid were added to DCM, reacted at 30°C for 4 days, the reaction solution was filtered, washed with 10% sodium sulfate solution, 10% sodium carbonate solution and distilled water in turn, and then dried over anhydrous magnesium sulfate, and then concentrated by rotary evaporation, washed with ether, and recrystallized to obtain compound B.
[0050] (2) Compound B, tetraethylammonium bromide, and dichloromethane were added to dichloromethane in a ratio of 1 g:0.15 g:5 mL. The mixture was then transferred to a high-pressure reactor and CO was introduced under nitrogen protection. 2 The pressure in the autoclave was raised to 5 MPa, and the mixture was stirred at 120 °C for 22 h. After the autoclave was cooled to room temperature, the remaining CO was released. 2 The mixture was reduced to normal pressure, washed with dichloromethane, and then dried in a vacuum oven at 30°C for 24 h to obtain compound C.
[0051] (3) Compound C, 1,6-hexanediamine and DMF were placed in a three-necked flask according to the ratio of 1 g: 0.4 g: 0.5 mL, and reacted at 158°C in a nitrogen atmosphere for 30 h, washed with deionized water, and then dried in a vacuum oven at 80°C for 24 h to obtain the obtained bio-based polyurethane. GPC: Mn of the obtained bio-based polyurethane is 5732 g / mol.
[0052] The preparation method of the above-mentioned modified dolomite is as follows:
[0053] According to the dosage ratio of dolomite and calcium lignin sulfonate solution of 1g:55mL, the dolomite is dispersed in the calcium lignin sulfonate solution with a concentration of 1g / L and the pH is adjusted to 9, and the mixture is stirred and reacted at room temperature for 24h, and then filtered and dried to obtain the product.
[0054] Example 2 also provides a method for preparing the polyurethane composite material for power transmission towers, which is as follows:
[0055] According to the above weight ratio, polyurethane, bio-based polyurethane, glass fiber, modified dolomite, graphene, sodium stearate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and Taoxi 3527 are mixed evenly in a stirrer, stirred at 175° C. and 500 rpm for 10 hours, and then poured and cured to form.
[0056] Example 3
[0057] Example 3 provides a polyurethane composite material for transmission towers, which is composed of the following raw materials, in parts by weight: 45 parts of polyurethane, 10 parts of bio-based polyurethane, 25 parts of glass fiber, 1 part of modified dolomite, 0.1 part of graphene, 0.1 part of sodium stearate, 0.5 part of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 1 part of Taoxi 3527.
[0058] The preparation method of the above bio-based polyurethane is as follows:
[0059]
[0060] (1) According to the mass ratio of chelidonic acid, 4-chloro-1-butene and triethylamine of 1:2:3, chelidonic acid, 4-chloro-1-butene and triethylamine were added to a mixed solution of DMSO and acetone (the volume ratio of DMSO and acetone was 1:2), and heated at 170°C for 36 hours. After the reaction, the precipitate was removed by filtration, and the acetone, triethylamine and unreacted 4-chloro-1-butene were removed by rotary evaporation, followed by extraction with dichloromethane, and washed with water to remove DMSO, dried over anhydrous magnesium sulfate, and rotary evaporated again to remove dichloromethane to obtain compound A; according to the mass ratio of compound A to meta-chloroperbenzoic acid of 1:2, compound A and meta-chloroperbenzoic acid were added to DCM, reacted at 25°C for 5 days, the reaction solution was filtered, washed with 10% sodium sulfate solution, 10% sodium carbonate solution and distilled water in turn, and then dried over anhydrous magnesium sulfate, and then concentrated by rotary evaporation, washed with ether, and recrystallized to obtain compound B.
[0061] (2) Compound B and tetraethylammonium bromide were added to dichloromethane in a ratio of 1 g:0.05 g:3 mL. The mixture was then transferred to a high-pressure reactor and CO was introduced under nitrogen protection. 2 The pressure in the autoclave was raised to 4 MPa, and the mixture was stirred at 110 °C for 26 h. After the autoclave was cooled to room temperature, the remaining CO was released. 2 The mixture was reduced to normal pressure, washed with dichloromethane, and then dried in a vacuum oven at 30°C for 24 h to obtain compound C.
[0062] (3) Compound C, 1,6-hexanediamine and DMF were placed in a three-necked flask according to the ratio of 1 g: 0.2 g: 0.3 mL, and reacted at 155°C for 24 h in a nitrogen atmosphere, washed with deionized water, and then dried in a vacuum oven at 80°C for 24 h to obtain the obtained bio-based polyurethane. GPC: Mn of the obtained bio-based polyurethane is 5191 g / mol.
[0063] The preparation method of the above-mentioned modified dolomite is as follows:
[0064] According to the dosage ratio of dolomite and calcium lignin sulfonate solution of 1g:45mL, the dolomite is dispersed in the calcium lignin sulfonate solution with a concentration of 1g / L and the pH is adjusted to 6. The mixture is stirred and reacted at room temperature for 36h, and then filtered and dried to obtain the product.
[0065] Example 3 also provides a method for preparing the polyurethane composite material for power transmission towers, which is as follows:
[0066] According to the above weight ratio, polyurethane, bio-based polyurethane, glass fiber, modified dolomite, graphene, sodium stearate, (3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and Taoxi 3527 are evenly mixed in a stirrer, stirred at 160° C. and 200 rpm for 12 hours, and then poured and cured to form.
[0067] Comparative Example 1
[0068] The difference between Comparative Example 1 and Example 1 is that dolomite is used instead of modified dolomite.
[0069] Comparative Example 2
[0070] The difference between Comparative Example 2 and Example 1 is that no bio-based polyurethane is added.
[0071] Comparative Example 3
[0072] The difference between Comparative Example 3 and Example 1 is that: no bio-based polyurethane is added, and the amount of modified dolomite is increased to 14 parts.
[0073] Comparative Example 4
[0074] The difference between Comparative Example 4 and Example 1 is that: no modified dolomite is added, and the amount of bio-based polyurethane is increased to 14 parts.
[0075] Comparative Example 5
[0076] The difference between Comparative Example 5 and Example 1 is that no bio-based polyurethane and modified dolomite are added.
[0077] Test example
[0078] The properties of the materials obtained in Examples 1-3 and Comparative Examples 1-5 were tested, and the specific test indicators and test methods are as follows:
[0079] Tensile strength and elongation at break: Tested in accordance with GB / T 528-2009, tested three times in parallel, and the results were averaged. For specific results, see Table 1;
[0080] Bending strength: refer to GB / T 9341-2000 for testing, test three times in parallel, and take the average value of the results. For specific results, see Table 1.
[0081] Table 1
[0082]
[0083] As shown in Table 1, the materials obtained in Examples 1-3 have excellent mechanical properties. Compared with Examples 1-3, Comparative Example 1 uses dolomite instead of modified dolomite; Comparative Example 2 does not add bio-based polyurethane; Comparative Example 3 does not add bio-based polyurethane and increases the amount of modified dolomite; Comparative Example 4 does not add modified dolomite and increases the amount of bio-based polyurethane; Comparative Example 5 does not add bio-based polyurethane and modified dolomite, and the mechanical properties of the materials obtained are all reduced. The above results show that the combination of bio-based polyurethane and modified dolomite can effectively improve the mechanical properties of polyurethane composites.
[0084] Analysis shows that lignin contains functional groups such as hydroxyl groups. Dolomite modified with lignin can interact with the polyurethane matrix and glass fiber, effectively improving the compatibility of dolomite with the polyurethane matrix, enhancing the filling effect of dolomite, and thereby increasing the mechanical properties of the polyurethane composite material.
[0085] The low molecular weight bio-based polyurethane prepared by the present invention contains functional groups such as hydroxyl groups and carbamates, which can interact with the polyurethane matrix to reduce the agglomeration force between polyurethanes, thereby improving its dispersibility; at the same time, the low molecular weight bio-based polyurethane has a shorter molecular chain and is more likely to interact with inorganic materials such as glass fiber, thereby improving the compatibility between the polyurethane matrix and the glass fiber, and can also form a stronger interface bonding force, thereby improving the mechanical properties of the polyurethane composite material.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.
Claims
1. A polyurethane composite material for a transmission tower, characterized in that: The polyurethane composite material comprises the following raw materials in parts by weight: 45-60 parts of thermoplastic polyurethane elastomer, 10-15 parts of bio-based polyurethane, 25-30 parts of glass fiber, 1-3 parts of modified dolomite, 0.1-0.5 parts of graphene, 0.1-0.5 parts of lubricant, 0.5-1.5 parts of antioxidant, and 1-3 parts of release agent; The preparation method of the bio-based polyurethane is as follows: (1) adding chelidonic acid, 4-chloro-1-butene, and triethylamine to a mixed solution of DMSO and acetone for heating reaction, and obtaining compound A after purification; adding compound A and meta-chloroperbenzoic acid to dichloromethane for reaction, and obtaining compound B after purification; (2) Compound B and tetraethylammonium bromide are added to dichloromethane, CO2 is introduced under nitrogen protection and stirred, and the mixture is washed and vacuum dried to obtain compound C; (3) Compound C and 1,6-hexanediamine are added to DMF for reaction, and then washed and vacuum dried to obtain; The preparation method of the modified dolomite is as follows: The dolomite is dispersed in the calcium lignin sulfonate solution and the pH is adjusted to 6-9, and the mixture is stirred and reacted at room temperature for 24-36 hours, and then filtered and dried to obtain the product.
2. The polyurethane composite material for power transmission towers according to claim 1, characterized in that: In step (2), the amount ratio of compound B, tetraethylammonium bromide and dichloromethane is 1 g: (0.05-0.15) g: (3-5) mL; the pressure of the reaction system is increased to 4-5 MPa by introducing CO2; the stirring temperature is 110-120° C., and the stirring time is 22-26 h.
3. The polyurethane composite material for power transmission towers according to claim 1, characterized in that: In step (3), the usage ratio of compound C, 1,6-hexanediamine and DMF is 1 g: (0.2-0.4) g: (0.3-0.5) mL; the reaction temperature is 155-160° C., and the reaction time is 24-32 h.
4. The polyurethane composite material for power transmission towers according to claim 1, characterized in that: The mass ratio of chelidonic acid, 4-chloro-1-butene and triethylamine in step (1) is 1:(2-3):(3-6); the volume ratio of DMSO and acetone in the DMSO-acetone mixed solution is 1:2; and the mass ratio of compound A and m-chloroperbenzoic acid is 1:(2-3).
5. The polyurethane composite material for power transmission towers according to claim 1, characterized in that: The temperature of the heating reaction in step (1) is 170-180°C, and the heating reaction time is 32-36 hours; the temperature of adding compound A and m-chloroperbenzoic acid to dichloromethane for reaction is 25-30°C, and the time is 4-5 days.
6. The polyurethane composite material for power transmission towers according to claim 1, characterized in that: The dosage ratio of the dolomite and the calcium lignin sulfonate solution is 1g: (45-55)mL; the concentration of the calcium lignin sulfonate solution is 1g / L.
7. The polyurethane composite material for power transmission towers according to claim 1, characterized in that: The antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, the release agent is Taoxi 3527, and the lubricant is sodium stearate.
8. The method for preparing the polyurethane composite material for power transmission tower according to claim 1, characterized in that: The following steps are involved: According to the weight ratio, the thermoplastic polyurethane elastomer, bio-based polyurethane, glass fiber, modified dolomite, graphene, lubricant, antioxidant and release agent are evenly mixed, stirred at 160-175° C. and 200-500 rpm for 10-12 hours, and then poured and cured to form.
Citation Information
Patent Citations
Nonisocyanate polyurethane synthesized by using carbon dioxide(CO2) as raw material
CN101812175A
High-strength heat-resistant cable and preparation method thereof
CN111499931A